Pemikiran Islamisasi Ilmu Pengetahuan Agus Purwanto dalam Buku Ayat-Ayat Semesta dan Nalar Ayat-Ayat Semesta. - Ummatun, Nurul, Dr. Sudarno Shobron, M.Ag, Dr. Syamsul Hidayat, M.Ag (2015)
slamization of science's discourse have been discussed since the last four decades. The source of the problem that we are facing now is caused by the destruction of knowledge. Knowledge that didn't have Islamic values has big impact in society. The project of islamization of science was emerged to solve this problem. This research is focus on Agus Purwanto's study in islamization of science and the development. The aims of this research are to know the thoughts of Agus Purwanto's Islamization of science in side his books, Ayat - Ayat Semesta and Nalar Ayat - Ayat Semesta, include his thoughts about contemporary islamization of science discourse. This is a library research with philosophy approach. The main sources of this research are Agus Purwanto's books, Ayat - Ayat Semesta and Nalar Ayat - Ayat Semesta, include direct interview with Agus Purwanto. The other sources are books, journals about islamization of science, etc. Analysis method that using in this research is induction, induction is study overall of these books deeply, thus take one conclusion about Agus Purwanto's thoughts about islamization of science. T he findings of this research is analyze of al Quran text as riil form to build the basic epistemology and science's theories that sourced from al-Qur'an and Hadith. The development of Agus Purwanto's thoughts have been implemented in study every branches of contemporary science, and moreover the thought have been implemented in Pesantren form